2017
DOI: 10.1002/adfm.201701466
|View full text |Cite
|
Sign up to set email alerts
|

Improved Interfacial Floatability of Superhydrophobic/Superhydrophilic Janus Sheet Inspired by Lotus Leaf

Abstract: Interfacial materials exhibiting superwettability have emerged as important tools for solving the real‐world issues, such as oil‐spill cleanup, fog harvesting, etc. The Janus superwettability of lotus leaf inspires the design of asymmetric interface materials using the superhydrophobic/superhydrophilic binary cooperative strategy. Here, the presented Janus copper sheet, composed of a superhydrophobic upper surface and a superhydrophilic lower surface, is able to be steadily fixed at the air/water interfaces, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
107
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(108 citation statements)
references
References 46 publications
0
107
0
1
Order By: Relevance
“…Cao and co‐workers found that the downside of the leaf is superhydrophilic while for the upside, due to the epicuticular wax crystalloids, it exhibits a great superhydrophobic property. Such special Janus wetting nature endows the lotus with such a prominent stability . The second is to choose cheap but excellent light absorb materials which can absorb sun light as much as possible and transform it to heat.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Cao and co‐workers found that the downside of the leaf is superhydrophilic while for the upside, due to the epicuticular wax crystalloids, it exhibits a great superhydrophobic property. Such special Janus wetting nature endows the lotus with such a prominent stability . The second is to choose cheap but excellent light absorb materials which can absorb sun light as much as possible and transform it to heat.…”
Section: Figurementioning
confidence: 99%
“…Such special Janus wetting nature endows the lotus with such a prominent stability. [13] The second is to choose cheap but excellent light absorb materials which can absorb sun light as much as possible and transform it to heat. For this purpose, extensive works have been performed by utilizing different kind of materials including metals, [7,[14][15][16] carbon based materials, [17][18][19][20] organic polymers, [21,22] and semiconductor nanoparticles.…”
mentioning
confidence: 99%
“…Fabrics with directional water transport ability across the thickness have received much attention owing to the smart moisture management capability useful for sportswear, workwear, health/aged cares, and defense. Two main strategies have been developed to prepare directional water transport fabrics: 1) creating a hydrophobicity‐to‐hydrophilicity gradient through fabric thickness, and (2) combining a layer of hydrophobic fibers with a layer of hydrophilic fibers . Wang and Zhou et al from our group have reported a series of methods to prepare directional water transport fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Recently,m any reports focus on ways to achieve directional water transportation along as olid surface by constructing well-defined architectures and/or performing chemical modifications. [14] Nevertheless,a ctive movement of water in immiscible oils seems not to have been reported, so far.…”
Section: Introductionmentioning
confidence: 96%